2018
DOI: 10.2478/pielxxiw-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Stress coping styles and occupational burnout syndrome of nurses employed in intensive care units

Abstract: Aim. The aim of the study is to evaluate a relationship between demographic and work-related factors and a work stress coping style as well as a relationship between a work stress coping style and symptoms of occupational syndrome. Material and methods. Material was collected from 50 nurses employed in intensive care units of clinical hospitals of the Medical University of Lodz. The study was conducted as a diagnostic survey using the following survey techniques: author’s questionnaire and the Coping Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Kotarba and Borowiak (2018) showed that the value of task-oriented style among the nurses surveyed varied depending on age. The data obtained in the present study did not correspond with these results [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Kotarba and Borowiak (2018) showed that the value of task-oriented style among the nurses surveyed varied depending on age. The data obtained in the present study did not correspond with these results [ 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The higher the educational level of nurses, the more often they used the task-oriented stress coping style. Kotarba and Borowiak (2018) also confirmed this relationship, indicating that nurses with higher educational levels cope better with occupational stress by using the task-oriented style [ 18 ].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Poland, little is known about symptoms of anxiety and depression among intensive care unit physicians; thus, a systematic comparison is difficult, and the data comprehensively describe far more the issue of professional burnout of ICU medical staff [11,12] rather than recognize the anxiety and depression levels at work, especially of critical care physicians.…”
Section: Introductionmentioning
confidence: 99%